Protective Effects of Live Combined B. subtilis and E. faecium in Polymicrobial Sepsis Through Modulating Activation and Transformation of Macrophages and Mast Cells - Guo, Lisha; Meng, Mei; Wei, Yaping; Lin, Feixue; Jiang, Ying; Cui, Xianzhen; Wang, Guirong; Wang, Chunting; Guo, Xiaosun (Frontiers in Pharmacology, 2019)
Aims: Clinical studies showed that the use of probiotics during critical illness reduced nosocomial infection and improved clinical outcome. However, the functional mechanisms of probiotics is remains unclear. Therefore the aim of current study is to explore the protective effects and understand the underlying mechanisms for the beneficial effects of live combined Bacillus subtilis and Enterococcus faecium (LCBE) in cecal ligation puncture (CLP)-induced sepsis. Methods and Results: Seven-week-old C57BL/6J mice were divided into three groups: sham group (6 mice), CLP-control group (20 mice, pretreatment with saline for 7 days before CLP surgery) and CLP-probiotics group (14 mice, pretreatment with LCBE enteric-coated capsules for 7 days before CLP surgery). In survival experiment, mice were monitored for 7 days after CLP. After the procedure, mice were sacrificed, and, serum, and peritoneal lavage fluid were collected and intestinal ileal samples were harvested. Results: Our results showed that the mortality was significantly reduced in mice CLP-probiotics group vs. CLP-control group (P < 0.05). Also, treatment CLP-probiotics group decreased the injury scores CLP-probiotics group when compared to CLP-control group. Additionally, levels of pro-inflammatory cytokines IL-6 and TNF-α levels in the serum and intestinal ileal tissues of CLP-probiotics group were reduced when compared to CLP-control group (P < 0.05). However, no significant differences in anti-inflammatory levels of IL-10 and TGF-β1 were observed between CLP-control and CLP-probiotic groups. Furthermore, our experiments showed that that probiotic treatment suppressed the macrophage activation and transformation from M-type to M1-type, inhibited the mast cells (MCs) degranulation, and activation of AKT (kinase B) pathway. Conclusion: In conclusion, our data shows that probiotics have a protective role in CLP septic mice through reducing intestinal inflammation, altering macrophage polarization and MCs degranulation, and regulating AKT signaling. Significance and Impact of Study: This study demonstrated the protective effects and mechanisms involved in the protective role of live combined Bacillus subtilis and Enterococcus faecium (LCBE) in CLP-induced septic mice model.